FACTORS INFLUENCING COMMUNITY PREFERENCE TOWARDS LOLONG BELANTI BMT - Siska Fitrima Sari; Fikra, Fikra (Journal of Social and Economics Research, 2025)
This study aims to determine the factors that influence people's preferences towards Baitul Mal Wattamwil Lolong Belanti. This study used quantitative methods using basic and intermediate level data. The analysis tool used is multiple linear to determine hypotheses using SPSS applications. The sample of this study consisted of members of BMT Lolong Belanti who were interested in BMT Lolong Belanti services. While the sample size used was 100 people who were sampled using purposive sampling techniques. The results of this study partly show: Vaiabel socialization has a significant positive effect on people's preferences for BMT Lolong Belanti. Promotion variables have a positive and significant effect on people's preference for BMT Lolong Belanti. Therefore, it can be concluded that.